Establishment of an Olfactory Region-specific Intranasal Delivery Technique in Mice to Target the Central Nervous System - Flamm, Johannes; Hartung, Sunniva; Gänger, Stella; Maigler, Frank; Pitzer, Claudia; Schindowski, Katharina (Frontiers in Pharmacology, 2022)
We have recently developed a region-specific catheter-based intranasal application method in mice by using CT scan-based 3D cast models of the murine nose (DOI: 10.2376/0005-9366-17102). This technique is able to deliver drugs specifically only to the olfactory region or only to the respiratory region. Thereby, intranasally administered drugs could be delivered either via neuronal connections to the central nervous system or via the well-perfused rostral parts of the nasal to the systemic circulation. In the present study, we transferred successfully this novel delivery technique to C57Bl/6 mice and determined parameters such as insertions depth of the catheter and maximum delivery volume in dependence to weight of the mouse. Breathing was simulated to verify that the volume remains at the targeted area. A step-by-step procedure including a video is presented to adopt this technique for standardized and reproducible intranasal CNS delivery studies (DOI: 10.3390/pharmaceutics13111904).